Biomethanation Of Palm Oil Mill Effluent (POME) By Ultrasonic-Membrane Anaerobic System (UMAS) - Nour, A. H.; Sangeethavani, Sundarajan (AENSI Publishing, 2017)
Palm Oil Mill Effluent (POME) is the wastewater produced during the production of palm oil. POME is a brownish, colloidal suspension that can cause severe damage to environment because of its high chemical oxygen demand (COD) and biochem ical oxygen demand (BOD). POME often released at high temperature (70 - 80°C) and has pH values between 3.5 and 4.5. In this study, Ultrasonic - Membrane Anaerobic system was used as a cost - effective design to treat POME while methane gas was collected from th e biomethanation process. POME was continuously feed into an anaerobic reactor and pH was maintained at 1.75 bar. Temperature was maintained between 30 and 35°C. Samples from reactor and permeate were collected after 5 hours of operation for the analysis o f COD, BOD, total suspended solids (TSS) and volatile suspended solids (VSS). At the end of 5 hours operation, biogas was collected from the top of 200 litres of UMAS reactor using a designated syringe. Throughout the experiment, the COD and BOD removal ef ficiencies were 66.06% and 96.88% respectively. 94.24% of total suspended solids removal was achieved at 10 days of hydraulic retention time. The methane gas production efficiency was 83.61%. The membrane fouling problem reduced and the treatment of POME w as improved by UMAS introduction.